The Project Based Learning Model on Motivation and Learning Outcomes of Elementary Civic Education - Ridzky Iklasul Fariasih; Achmad Fathoni (Jurnal Ilmiah Sekolah Dasar, 2022)
One of the problems in the learning process for elementary school children is the lack of focus and concentration in learning because teachers often use conventional models and do not interactive. The failure to achieve mastery of learning is caused by students' weak understanding of the material being taught, and the lack of teacher creativity in developing learning models so that the learning outcomes obtained are less than optimal. The researcher aims to analyse the effect between the application of the Project Based Learning (PjBL) learning model and learning motivation of elementary students on learning outcomes in PPKn subjects. In this study the quantitative experimental method was used with the pretest and posttest experimental designs used. The sample used was 30 students. Data collection techniques is using a pretest-posttest and giving questionnaires to students. The data analysis technique uses a two-way analysis of variance to test the hypothesis. However, a requirement test was carried out, which included a normality test and a homogeneity test. Based on the analysis of the results, there is a relationship between applying the PjBL learning model and learning motivation on the learning outcomes of Civics subjects in elementary schools. It was concluded that applying the PjBL learning model and learning motivation could improve student learning outcomes.